2001
DOI: 10.1111/j.1745-4514.2001.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF MgCl2/SODIUM PYROPHOSPHATE ON CHICKEN BREAST MUSCLE MYOSIN SOLUBILIZATION AND GELATION

Abstract: Sodium chloride (0.29 M) at pH 7 solubilized about 24% of the myosin of washed, minced chicken breast muscle. At a similar pH, 0.2 M sodium chloride in the presence of 10 mM sodiumpyrophosphate and 10 mM magnesium chloride solubilized almost 60% of the myosin. In spite of the greater solubility of myosin under the latter conditions, when gels were prepared with these concentrations of salt at pH 7, the gels without the sodium pyrophosphate and magnesium chloride were slightly superior in both stress (39.3 kPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sodium chloride is the salt commonly used in commercial reformed meats. It is generally accepted that a high concentration (2% to 3%) of sodium chloride is required to solubilize the MPs and fully develop the functional properties of muscle tissue foods (Xiong and Brekke 1991), but Chang and others (2001a, 2001b) and Feng and Hultin (2001) concluded that solubilization of the MPs was not an absolute necessity for gel formation by MPs. Assuming that lean meat skeletal muscle contains 75% water, molar concentrations of salt calculated from those percentages (2% to 3%) give 0.47 to 0.68 M (Ishioroshi and others 1979).…”
Section: Ionic Strengthmentioning
confidence: 99%
“…Sodium chloride is the salt commonly used in commercial reformed meats. It is generally accepted that a high concentration (2% to 3%) of sodium chloride is required to solubilize the MPs and fully develop the functional properties of muscle tissue foods (Xiong and Brekke 1991), but Chang and others (2001a, 2001b) and Feng and Hultin (2001) concluded that solubilization of the MPs was not an absolute necessity for gel formation by MPs. Assuming that lean meat skeletal muscle contains 75% water, molar concentrations of salt calculated from those percentages (2% to 3%) give 0.47 to 0.68 M (Ishioroshi and others 1979).…”
Section: Ionic Strengthmentioning
confidence: 99%
“…[41,42] NaCl is fairly effective in solubilizing substantial amount of major myofibrillar proteins at 2.5% concentration. [42−44] For instance, ∼90% actomyosin proteins were solubilized from Pacific white shrimp at 0.2M NaHCO 3 .…”
Section: Variation In Solubilitymentioning
confidence: 99%